Antioxidant and Cytoprotective Potential of the Essential Oil Pistacia lentiscus var. chia and Its Major Components Myrcene and α-Pinene - Vasileios Xanthis; Eleni Fitsiou; Georgia-Persephoni Voulgaridou; Athanasios Bogadakis; Katerina Chlichlia; Alex Galanis; Aglaia Pappa (MDPI AG, 2021)
The antioxidant, cytoprotective, and wound-healing potential of the essential oil from the resin of Pistacia lentiscus var. chia (mastic oil) was evaluated, along with that of its major components, myrcene and α-pinene. Antioxidant potential was monitored as: (i) direct antioxidant activity as assessed by 2,2-di-phenyl-1-picrylhydrazyl (DPPH), 2,2-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), and ABTS assays; (ii) DNA damage protection activity; and (iii) cytoprotective activity as assessed via induction of transcription of genes related to the antioxidant response in human keratinocyte cells (HaCaT). The cytoprotective potential of the test substances was further evaluated against ultraviolet radiation B (UVB)- or H2O2-induced oxidative damage, whereas their regenerative capability was accessed by monitoring the wound closure rate in HaCaT. Μastic oil and major components did not show significant direct antioxidant activity, however they increased the mRNA levels of antioxidant response genes, suggesting indirect antioxidant activity. Treatment of HaCaT with the test substances before and after UVB irradiation resulted in increased cell viability in the cases of pre-treatment with mastic oil or post-treatment with myrcene. Increased cytoprotection was also observed in the case of cell treatment with mastic oil or its major components prior to H2O2 exposure. Finally, mastic oil and myrcene demonstrated a favorable dose-dependent effect for cell migration and wound closure. Collectively, mastic essential oil may exert its promising cytoprotective properties through indirect antioxidant mechanisms.